PROJECT FINANCE JAKO METODA FINANSOWANIA INWESTYCJI INFRASTRUKTURALNYCH - Jewartowski, Tomasz (Wydział Prawa i Administracji UAM, 2002)
For the time being there is no clear definition of project finance and there is no unanimity about the role of its specific characteristics as potentially distinctive traits. Empirical research leads to the following conclusions: - in order to realise an undertaking a special company is created, called a project company or a vehicle company (also: special purpose company), - the sponsors and shareholders in such a company are also companies which actively participate in the project e.g. as contractors or subcontractors, - project participants (contractors, managers, lenders, often governmental agencies, and, if possible, final users) all create a network of contracted connections aiming at distinguishing the possible types of risk and ascribing the consequences of those risks to particular parties, - a company implementing a project uses a high leverage and the creditors have limited rights to file a claim in the case of a failure of the project (limited-recourse or non-recourse financing). Most projects are realised in the industries that are particularly significant to the state, and in many cases a project cannot be launched without a permit from the special governmental agencies overseeing the investment process and representing the state interests while the buildings are erected and used. This article deals with two trends in the research on project finance. One of them focuses upon project finance as a method of financing virtually only investments in the infrastructure sphere and it includes research on the justification for private capital involvement in the infrastructure, in addition to research on the role of the state in implementing projects and on the effect of project finance upon the situation in the state where the undertaking is realised. The other trend perceives project finance as a method of financing investment in general and it aims at presenting the conditions for deriving greater benefits than in the case of carrying out undertakings by the company itself.
PROJECT FINANCE AS A METHOD OF FINANCING INFRASTRUCTURE INVESTMENTS